(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
In recent years, numerous studies have focused at the phenomenon of child sexual abuse (hereinafter, the CSA) offering valid conclusions about its phenomenological structures, etiological causes and impact on victims and society as a whole. Although the bulk of research has furthered our understanding of different aspects of CSA, scientific work that would focus on child victims’ rights from constitutional and criminal law perspective is still scarce. Seeking to fill the noted gap, the author presents the first academic study on standards for protection of sexually abused children’s rights set by the European Court for Human Rights (hereinafter, the ECtHR or the Court). Relaying on Faye Jacobsen set of blended methodologies, 10 judgments related to protection of rights of sexually victimised children are retrieved from the HUDOC system and analysed in detail. A special attention has been paid to safeguards and guarantees under the Article 3 and 8 of the Convention as well as their critical evaluation with respect to already established constitutional legal solutions. The qualitative analysis has revealed that judicial activism in the Strasbourg Court case law has been for years a driving force to enhance the protection of sexually abused children, and that today, this protection has significantly evolved, forming a concept of particularly vulnerable victims and child-sensitive approach within the context of child friendly justice. Although the evolutive line of the scope and content of CSA protection standards created by the Court can be noted, judicial reasoning techniques behind their development are susceptible to criticism.